1.3 μm optically-pumped monolithic VCSEL based on GaAs with InGa(Al)As superlattice active region. (1st July 2022) - Kryzhanovskaya, Natalia V; Likhachev, Alexey I; Blokhin, Sergey A; Blokhin, Alexey A; Pirogov, Evgeniy V; Sobolev, Maxim S; Babichev, Andrey V; Gladyshev, Andrey G; Karachinsky, Leonid Ya; Novikov, Innokenty I; Andryushkin, Vladislav V; Denisov, Dmitrii V; et al.
Abstract: Неre we report a monolitic long-wavelength vertical cavity surface-emitting laser based on GaAs with bottom GaAs/AlGaAs distributed Bragg reflectors (DBRs), metamorphic optical cavity with In0.41 Ga0.59 As/In0.25 Ga0.75 As-active region providing emission near 1.3 μ m with high modal optical gain and top dielectric SiO2 /Ta2 O5 DBRs. We achieve continious wave single-mode operation at room temperature under optical pumping. The proposed approach has potential for high output power and high temperature (up to 200 °C) stable operation.